2008
DOI: 10.1074/jbc.c800108200
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of MicroRNA Processing Inhibition by the Developmentally Regulated RNA-binding Protein Lin28

Abstract: The developmentally regulated RNA-binding protein Lin28 blocks processing of let-7 family microRNAs (miRNAs) in embryonic cells. The molecular basis for this selective miRNA processing block is unknown. Here we find that Lin28 selectively binds the terminal loop region of let-7 precursors in vitro and that the loop mediates miRNA processing inhibition in vivo. Additionally, we identify the domains of Lin28 required for this inhibition. These findings establish a regulatory role for the terminal loop of precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
291
2
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(310 citation statements)
references
References 33 publications
13
291
2
3
Order By: Relevance
“…Consequently the cleavage by Drosha would be blocked, and the maturation process is thereby inhibited. Piskounova et al showed that some Drosha inhibitors such as Lin28, selectively bind to the terminal loop region of miRNA precursors and mediate the miRNA procession [53,54]. Thus, it is also possible that the [A]-[G] variant changes the binding affinity of some Drosha inhibitors and consequently affects the processing of miR-27a.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the cleavage by Drosha would be blocked, and the maturation process is thereby inhibited. Piskounova et al showed that some Drosha inhibitors such as Lin28, selectively bind to the terminal loop region of miRNA precursors and mediate the miRNA procession [53,54]. Thus, it is also possible that the [A]-[G] variant changes the binding affinity of some Drosha inhibitors and consequently affects the processing of miR-27a.…”
Section: Discussionmentioning
confidence: 99%
“…An additional Lin-28 homolog, Lin-28B, was identified as a highly expressed gene in hepatocellular carcinoma cells (41). Recently, Lin-28 and Lin-28B were demonstrated to function as negative regulators of let-7 biogenesis (30)(31)(32)(33)(34). These proteins are members of a highly conserved family of orthologous RNA binding proteins that contain a cold shock domain and dual zinc fingers.…”
Section: Discussionmentioning
confidence: 99%
“…Piskounova et al (50) have clearly shown that LIN28 selectively binds the terminal loop region of precursor let-7g miRNAs (i.e., both pri-and pre-let-7g sequences) and mature let-7g localized primarily to the cytoplasm (51). It has also been shown that the expression of LIN28B and less frequently LIN28 is activated in several cancer types and their overexpression causes cellular transformation (6) along with increased c-Myc, HMGA2, and ras expression (52).…”
Section: Potential Cooperative Activities Of Rps2 and Lin28bmentioning
confidence: 99%